Generalized reduced-form auctions: A network-flow approach - Yeon-Koo Che; Jinwoo Kim; Konrad Mierendorff (University of Zurich, Department of Economics, 2013)
We develop a network-flow approach for characterizing interim-allocation rules that can be implemented by ex post allocations. Our method can be used to characterize feasible interim allocations in general multi-unit auctions where agents face capacity constraints, both ceilings and floors. Applications include a variety of settings of practical interest, ranging from individual and group-specific capacity constraints, set-aside sale, partnership dissolution, and government license reallocation.
Keywords: D44; 330; reduced-form auctions; network-flow approach; feasible circulation flow; paramodular capacity constraints; Auktion; Allokation; Auktionstheorie